Kerjasama Pemerintah Republik Afrika Tengah dan UNICEF dalam Menangani Kasus Perekrutan Tentara Anak di Republik Afrika Tengah - Kristy, Rahellia Bayu Stella; Pattipelohy, Shary Charlotte (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Continous humanitarian crisises in the Central African Republic are instigated by the armed conflicts involving underage combatants also known as child soldiers. Set against this phenomenon, the Goverment of Central African Republic is trying to overcome the issue by initiating collaboration with UNICEF, hoping to put an end to the use and recruitment of said underage soldier operating and fighting throughout the territory of the Central African Republic. The objective of this research is to analyze the existing collaboration between the Republic of Central Africa and UNICEF by firstly, describing the conflict in the Central African Republic and then followed by tabling the factors that enable the recruitment of the children of the war, and as well providing anlayses on the UNICEF’s role in hattling the case of child soldier recruitment and the obstacles that the organization has to endure from its attempt of doing so in the region of Central African Republic. This research employs qualitative method by collecting data from books, NGO’s reports, and mass media. The explanation about the collaboration between UNICEF and the Central African Republic is given by utilizing the standpoint of Liberalism together with the perspectives of the concepts of Cooperation and International Organization, respectively. This research concludes that the presence of a number of obstacles in the collaborative work between UNICEF and the Goverment of Central African Republic has been the primary reason that made the collaboration between the two actors, arguably, has not been entirely and fully succesful.